The Radiology Fellowship Application and Selection Process in the United States: Experiences and Perceptions from Both Sides - Hyojeong Mulcahy; Felix S. Chew; Michael J. Mulcahy (Radiology Research and Practice)
Objective. Our purpose was to investigate radiology fellowship directors' and recent fellows' experiences and perceptions with regard to the fellowship application and selection process and to compare these experiences and perceptions. Materials and Methods. Institutional review board approval was obtained. We conducted an online survey of the memberships of three radiology subspecialty societies between October 2009 and December 2009 to learn about radiologists' views regarding various aspects of radiology fellowships. Results. In the process of selecting fellows, program directors and recent fellows consider performance during the radiology residency and the quality or prestige of the residency program as the most important objective factors, and the personal interview, letters of recommendation, and personality as the most important subjective factors. 25% of the program directors were in the match, and 41% of the recent fellows were in the match. Most (48%) of program directors favored a match, but most (56%) of the recent fellows disfavored participating in a match. Both program directors and recent fellows expressed satisfaction with the fellowship application and selection process. Conclusion. There was no majority support for a fellowship match among program directors and recent fellows and less support among recent fellows. Recent fellows appear more satisfied with the current selection and application process than program directors.